SWOT Analysis of Noodle Shop Product Business Development 81 During the Covid 19 Pandemic - Christina, Vanesa; G. Soedarsa, Herry (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2022)
The culinary business is one of the rising businesses that are also in great demand by entrepreneurs in Bandar Lampung. That’s proved an increasing numbers from culinary businesses in Bandar Lampung. The impacts covid-19 virus has made by economic on Bandar Lampung City experience drastic decline, especially in the culinary field. One of the noodle shops in Bandar Lampung is Kedai Mie 81. This research intends to analyse the right marketing strategy for Kedai Mie 81 to increase revenue. The sample of this research will use Kedai Mie 81 and Mie Ajan as a comparison. The number of noodle shops used are two shops using data that will be collected from interviews and questionnaires to owners and customers from the sample. The results explained that Kedai Mie 81 has more strategic location, economical prices, and satisfactory service compared to Mie Ajan. The analysis of the Cartesian SWOT tells that Kedai Mie 81 is in quadrant 1 where the right marketing strategy needs to be done. Also the SWOT matrix analysis explains that the largest value obtained by SO is 3.7 where it is very necessary to carry out marketing strategies through offline and online media.